Posttraumatic stress and depression symptom classes in parents of trauma-exposed children: a transdiagnostic perspective using pooled individual participant data - Yaara Sadeh; Leila Graham; Michael Curtis; Melissa Janson; Jeeeun Kim; Ashlyn Schwartz; Andrea Undset; Anna Denejkina (European Journal of Psychotraumatology, 2024)
ABSTRACTBackground: In the aftermath of child trauma, post-traumatic stress (PTS) and depression symptoms often co-occur among trauma exposed children and their parents. Studies have used latent class analysis (LCA) to examine PTS and depression symptoms and identify homogeneous subgroups among trauma exposed children. However, little is known about subgroups or classes of PTS and depression reactions of parents of traumatised children.Objectives: (1) Determine PTS and depression symptom classes at 2–9 months post-trauma, and (2) to examine sociodemographic covariates among parents of trauma exposed children.Methods: Using harmonised individual participant data (n = 702) from eight studies (Australia, UK, US) included in the Prospective studies of Acute Child Trauma and Recovery Data Archive (PACT/R), we modelled these phenomena at the symptom level using LCA.Results: Our LCA yielded three solutions: ‘high internalizing symptom’ class (11%); ‘low PTS-high depression’ class (17%); and ‘low internalizing symptom’ class (72%). Parents of children in the ‘low PTS-high depression’ class were more likely to have children of older age and be part of an ethnic minority, compared to the ‘low internalizing symptoms’ class. Mothers were more likely to be in the ‘high internalizing symptom’ class compared to the ‘low internalizing symptoms’ class.Conclusions: These findings reveal a qualitative structure and relationship between depression and PTS symptoms that highlights the importance of assessing and targeting a broad range of internalising symptoms in post-trauma psychological treatment.